Production and characterization of cellulases and hemicellulases from a consortium between Pleurotus ostreatus and Aspergillus niger cultured in agro-industrial wastes - Martins, Igor Magno Nicurgo Borges Rosa (2021)
The enzyme biosynthesis using agricultural wastes by solid state fermentation (SSF) and the study of their physicochemical properties are meaningful approaches to improve the biomass hydrolysis. Among them, β-glucosidases and β-xylosidases are key enzymes at the lignocellulose depolymerization, which act in the cleavage of oligosaccharides in monosaccharides. In this study, the production of hemicellulases and cellulases by Pleurotus ostreatus and Aspergillus niger monocultures or in consortium was investigated, using raw sugarcane bagasse (SB) and wheat bran (WB) as substrates. The highest enzymatic activities were observed in the crude extract produced by P. ostreatus PLO6 and A. niger SCBM4 consortium with 98.5, 62.9, 3.8, 12.4, 13.3 and 20.2 U/g for β-glucosidase (β-glu), β-xylosidase (Bxyl), filter paper cellulase (FPase), xylanase (Xyl), exoglucanase (Exgl) and endoglucanase (Engl), respectively. The pH and temperature effects on β-glu and β-xyl were characterized. Optimal activities were obtained at pH 4.0 and 45 °C for β-glu and 3.5 and 55 °C for β-xyl. Both enzymes were stable at acid pH and presented thermostability. The results indicated that the enzymatic cocktail demonstrated potential characteristics for future applications in saccharifications. The use of sugarcane bagasse and wheat bran for microbial growth contributed to aggregate value to these byproducts.